A Parent-to-Parent Program in Taiwan. Issue 2 (April 2018) - Liu, Kae
Abstract : Parent-to-parent programs provide emotional and informational support to parents of children with special needs by matching trained and experienced parents with parents needing support. This study examined the implementation and effects of a Parent-to-Parent Program in Taiwan that supported 3 families of youngsters with special needs. Based on the individual family's needs and the availability of local resources, these families were supported by 2 trained and experienced mothers of children with special needs, the staff of the family-centered early intervention center as well as the self-help parent group, and a researcher. Notwithstanding the myriad of criteria considered when matching the families before the program implementation, the fitness of the match would ultimately be determined on the basis of the initial contact or subsequent interactions between families. During the program implementation, this study found the following: (1) "natural" and well-prepared initial contact facilitated subsequent relationships; (2) understanding real needs was the key; (3) "being present" was a form of support; and (4) experienced parents could help "translate" professionals' recommendations. After the program was implemented, experienced parents needed support, too. This study concludes that "localization" is the key in implementing parent-to-parent programs. Furthermore, with more people involved in the program, trained professionals will no longer exert a dominant influence and more members of the families' informal support network can be empowered.